2018
DOI: 10.4028/www.scientific.net/kem.775.448
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Laser Beam Welded Al<sub>0.5</sub>CoCrFeNi High-Entropy Alloy

Abstract: High-entropy alloys (HEA), a new generation alloy system offer superior mechanical properties with solid solution strengthening. AlxCoCrFeNi-HEA is one such system being received more attention because of its specific yield strength and ductility. In the present work, Al0.5CoCrFeNi-HEA was prepared by vacuum arc melting. The laser beam welding (LBW) was carried out on 1mm thick forged and homogenized HEA, with a beam power of 1.5 kW and at a traverse speed of 600 mm/min. The microstructural features of differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 19 publications
1
13
0
Order By: Relevance
“…For Al0.5CoCrFeNi, the elemental analysis in FZ revealed that the dentrites were rich in Fe and Co, depleted of Al and Ni, and had an even distribution of the Cr element [ 19 ]. Similar results have been observed in LBE of Al0.5CoCrFeNi [ 30 ]. It is not fully clear if evaporation of Al had played role influencing the structure and properties.…”
Section: Grain Structure Element Distribution and Precipitations supporting
confidence: 90%
See 3 more Smart Citations
“…For Al0.5CoCrFeNi, the elemental analysis in FZ revealed that the dentrites were rich in Fe and Co, depleted of Al and Ni, and had an even distribution of the Cr element [ 19 ]. Similar results have been observed in LBE of Al0.5CoCrFeNi [ 30 ]. It is not fully clear if evaporation of Al had played role influencing the structure and properties.…”
Section: Grain Structure Element Distribution and Precipitations supporting
confidence: 90%
“…For HEAs, hardness drop in the FZ was observed for Al0.5CoCrFeNi in laser and arc welding, while the hardness drop for CoCrFeMnNi is relatively limited or slightly increased. Sokkalingam et al [ 19 , 30 ] suggested that the hardness drop for the Al0.5CoCrFeNi in the LB weldment was due to the reduction of the hardening factor (Al-Ni rich BCC phase) in the weld metal than in the base metal. The processing method of the sample also influences the hardness changes.…”
Section: Discussion and Future Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Researchers around the globe are extensively working on HEA research, and designing HEAs to tailor and improve the properties of the engineering materials [25][26][27]. One such application is the use of HEA as a reinforcement/binder in the metal matrix composites [28][29][30].…”
Section: Introductionmentioning
confidence: 99%